A brief insight into Citrobacter species - a growing threat to public health - Jabeen, Ishrat; Islam, Sohidul; Hassan, A. K. M. Imrul; Tasnim, Zerin; Shuvo, Sabbir R. (Frontiers in Antibiotics, 2023)
Citrobacter spp. are Gram-negative, non-spore forming, rod-shaped, facultative anaerobic bacteria from the Enterobacteriaceae family often found in soil, sewage, sludge, water, food, and the intestinal tracts of animals and humans. Several members of Citrobacter spp. especially C. freundii, C. koseri, C. braakii are frequently detected in newborn illnesses, urinary tract infections, and patients with severe underlying conditions, including hypertension, diabetes, cancer, and respiratory infections, or those who are immunocompromised. Strains of Citrobacter spp. can spread vertically or horizontally from carriers or other hospital sources and thus cause nosocomial infections in hospital settings. A total of 19 Citrobacter genomospecies have been recognized based on genomics. It has been noted that the Citrobacter genus acquired antimicrobial resistance and virulence, including invasion, colonization, biofilm formation, and toxin production. The recent emergence and spread of antimicrobial resistance to β-lactams, carbapenems, fluoroquinolones, aminoglycosides, and colistin in Citrobacter spp. through chromosomal and plasmid-mediated resistance limits the empiric treatment options. Therefore, combination therapy involving costly and potentially hazardous antibiotics poses significant challenges in treating Citrobacter infections. Here we summarized the nomenclature of Citrobacter spp., clinical manifestations, epidemiology, pathogenesis, antibiotic resistance mechanisms, and treatments from various clinical samples. This review will expand our knowledge of the genomics and epidemiology of Citrobacter spp., enabling improved control of infections and the spread of these organisms.